2012
DOI: 10.4172/2167-7956.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Production of Hyaluronidase by Streptococcus mitis MTCC 2695

Abstract: Hyaluronidase was produced by submerged fermentation from Streptococcus mitis. The possibility of using Streptococcus mitis for enzyme production has been recently investigated. In this study, the physical and nutritional parameters were optimized to improve the production of hyaluronidase by Streptococcus mitis and it was accessed. Maximum production of hyaluronidase was obtained when 5% starch supplemented as carbon source achieved by employing (98.7U/ml) and followed by ammonium chloride (140.4U/ml) incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The selected isolate was cultured in 50 ml medium Erlenmeyer flasks and incubated at different temperatures, 25 °C, 30 °C ,37 °C and 45 °C. All flasks were shaking incubated at 150 rpm for 24 h. The cell free centrifugate was obtained at 4000 rpm centrifugation for 30 min using Beckman centrifuge (Model-Avanti™ -25 Beckman Co., U.S.A) and used for enzyme assay [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected isolate was cultured in 50 ml medium Erlenmeyer flasks and incubated at different temperatures, 25 °C, 30 °C ,37 °C and 45 °C. All flasks were shaking incubated at 150 rpm for 24 h. The cell free centrifugate was obtained at 4000 rpm centrifugation for 30 min using Beckman centrifuge (Model-Avanti™ -25 Beckman Co., U.S.A) and used for enzyme assay [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The suitable fermentation period supporting the maximum production of enzyme was investigated at different periods, 16,24, 48, 72 and 96 h at 150 rpm [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies revealed that hly plays a significant role in producing proinflammatory cytokines (Campo et al, 2012). Furthermore, hly is a means of enhancing mobility across the body's tissues, and as an antigenic distinguish that prevents their being recognized by phagocytes of the immune system (Mahesh et al, 2012). as a result, hly is an important factor in the pathogenicity of GBS.…”
Section: Detection Of Hly Genementioning
confidence: 99%
“…Hyaluronidases are naturally found in mammals, insects, leaches and bacteria (Bertolami & Donoff, 1982). Several prokaryotic microorganisms produced hyaluronate lyases as Streptomyces (Laurent & Fraser, 1992), Staphylococcus (Ahmed, 2014) and Streptococcus (Mahesh et al, 2012) were different in substrate specificity. Different sources of hyaluronidases vary in their molecular weight, based on substrate specificity, pH optima and catalytic mechanism (Yingprasertchai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%